Regional Financial Market Integration: Learning from the European Experience - Benn Steil (Inter-American Development Bank, Office of the Chief Economist, 1997)
The so-called European model of market integration has evolved over many decades. In particular, the original plan to integrate Europe economically via a progressive program of harmonizing national legislation has, particularly in the area of financial markets, given way to a radical alternative based upon Member State mutual recognition of existing national legislation and regulation. Whereas this shift had been initiated largely on pragmatic grounds, the mutual recognition approach has since taken on an ideological and strategic dimension in political negotiations which makes the study of its effects on the ground all the more important.
Keywords: 330; Regionaler Finanzsektor; Marktintegration; Regulierung; EU-Staaten